Sistem Kendali Level dan Suhu Air pada Hidroponik menggunakan Sensor Ultrasonik, Sensor Suhu, dan Arduino dengan Metode Regresi Linier - Muhammad Rizki Chairurrafi; Hurriyatul Fitriyah; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Hydroponics is a method of farming in which the growing media does not use soil but uses nutrient water needed by plants. There are several factors for the quality of the plants grown hydroponically are fresh and healthy. By controlling the height and temperature of the nutrient water in the hydroponic tub. The control process uses Arduino Uno ATMega328, the for the water level reading system using ultrasonic sensor HC-SR04 and reading the water temperature using a water temperature sensor DS18B20. The output for the water level is a water pump and for the water temperature is a cooling system using Peltier TEC1-12706 as the water cooling component. This research uses a simple linear regression method that functions to predict the duration of the system. The result of this study for the water level feature have a set point of 2,8 cm and the linear regression equation y = 9.71756x - 56.0144 then for the MAPE value is 6.097%. For the water temperature feature have a set point of 28Â°C and the linear regression equation y - 712.56386 - 19746.65866 then for the MAPE value is 6.3134%. And the computational value to get the duration or y value for the two features obtained from each simple linear regression equation is 1081 mx or 1.081 seconds.